A MULTICENTER, RANDOMIZED, DOUBLE-BLIND, AND CONTROLLED STUDY OF TREATMENT WITH HYDROCORTISONE-ETHANOL GEL OINTMENT IN CHILDREN’S WITH MODERATE-TOSEVERE ATOPIC DERMATITIS - BHABHOR, ARTI; HARSH OZA, RUTU; MAKWANA, PRATIK; Tralsawala, Krunal (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective is to see the effectiveness of hydrocortisone (HC)-ethanol gel (EG) ointment in treating children with Moderate-to-severe atopic dermatitis (AD). Methods: Thirty children with moderate-to-severe AD participated in a 2-week double-blind, randomized, and controlled clinical trial. They were randomly assigned to apply either an ointment with 1% HC ointment or a novel ointment containing 1% HC and dispersed EG droplets HC. At the end of 2 week, SCORAD score was measured. SCORAD is a clinical tool used to assess the extent and severity of eczema (SCORing AD). Results: A 2-week double-blind, randomized, and controlled clinical trial included 30 kids with moderate-to-severe AD. About 1% HC ointment or a new ointment comprising 1% HC and dispersed EG droplets were applied to them at random (HC-EG). The SCORAD score was calculated at the conclusion of 2 weeks. A clinical tool called SCORAD is used to evaluate the severity and extent of eczema (SCORing AD). Conclusion: We would want to draw the conclusion from our research that HC-EG ointment was superior to HC ointment in terms of reducing AD-related pruritus and visible rash.